Crop and Livestock Depredation by Wild Animals: The Case of Ranthambore Tiger Reserve, India - Deepak Chand Meena; B.S. Meena, Sanchita Garai, H.R. Meena, Gopal Sankhala, Akshita Chadda (Indian Journal of Extension Education, 2022)
People worry about crop and livestock destruction by wild animals in the nearby protected region, which might lead to opposition to the preservation of a protected area. We surveyed 360 households from 30 villages in the eco-sensitive region of Ranthambore Tiger Reserve in the period of December 2021 to May 2022 to assess the annually loss in the crops by the wild animals and livestock attacked by the wild animals. One-way variance followed by DMRT post hoc was used to analyse losses in crop. It was observed that farmers getting losses, in Rabi season farmers get much loss in the mustard crop, and in Kharif season farmers get loss in maize crop due to wild animals in the form of crop raiding foraging, and eating. 335 number of incidents happened with livestock in the last five years among them 155 got injured and 180 were killed by wild animals, majority of incidents happened with goat followed by calves and buffalo. Our comparative analysis helps to further ongoing conservation and compensation efforts by shedding light crops and livestock that influence conflict loss and tolerance.